FAMILY NEEDS FULFILLMENT AMONG POOR SINGLE MOTHERS IN URBAN INDONESIA: A QUANTITATIVE STUDY IN EAST JAKARTA: A Quantitative Study in East Jakarta - Bambang Rustanto; Tuti Kartika; Pribowo; Ayi Haryani; Aryohaji Istyawan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The increasing number of single mothers who are required to perform dual roles as breadwinners and family caregivers has become an important social issue, particularly among poor families in urban areas. This study aims to analyze family needs fulfillment among Poor Single Mothers in Gedong Village, Pasar Rebo District, East Jakarta, Indonesia. The study employed a descriptive method with a quantitative approach. Data were collected through questionnaires distributed to 30 working single mothers aged 19–59 years. The data were analyzed descriptively through editing, coding, tabulation, and interpretation processes based on actual and ideal scores for each aspect of family needs fulfillment. The findings indicate that physical needs fulfillment was categorized as fulfilled with a percentage of 82.93%, emotional needs fulfillment reached 79.00%, and educational needs fulfillment reached 74.57%. Meanwhile, economic needs fulfillment obtained a percentage of 72.09% and was categorized as less fulfilled. These findings demonstrate that Poor Single Mothers were generally able to fulfill the basic needs of their families; however, they still experienced economic vulnerability due to limited income, high household expenditures, and limited access to social assistance. Therefore, social support and economic empowerment are necessary to improve the sustainable well-being of Poor Single Mothers and their families.